The role of geography in the analysis of industrial development strategies within the spatial organisation of a region - Wali, Ayad Ayid (Bulletin of Geography. Socio-economic Series, 2014)
Through presenting the main axes in this study, it is clear that identifying a precise concept of industrial development is related to a wider idea of development. Despite that, the geographical view gives a wider and more comprehensive concept of the industrial development. Moreover, balanced spatial development is closely related to industrial and agricultural development within the space of a geographical region. Industry and agriculture represent productive activities which form the economic basis for a region. Industrial development is the most important tool which is used in developing rural areas. Moreover, industrial development has a great role in developing other activities, especially services in a region. This is done through the capability of industry to provide requirements of other activities and absorb labour force surplus from other economic sectors. In addition, the industry sector increases economic revenues for the region and raises the individuals’ incomes. Strategies of achieving industrial development spatially differ from region to region. This relates to a group of variables, such as political and economic conditions in a region, its development, as well as size of industrial investments. However, accomplishing industrial development spatially requires putting appropriate developmental strategies which conform with a region’s development level and available industrial investments, particularly, in underdeveloped regions with limited financial resources. These regions need to be identified as the most underdeveloped ones in order to attract industrial investments according to the unparalleled spatial development model. What should be taken into consideration is focus on adopting the modern technological development of industry in the field of spatially achieved industrial development through providing appropriate spatial elements. This should be followed by the distribution of modern industrial projects of large production capacity which exploit ideally the available geographical qualifications to attain big economic revenues that supports and develop other economic activities. This is reflected positively in the balanced spatial development of a geographical region.